2006
DOI: 10.1093/ecam/nel006
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents of Brazilian Red Propolis

Abstract: In a new propolis type, red Brazilian propolis, 14 compounds were identified (six of them new for propolis), among them simple phenolics, triterepenoids, isoflavonoids, prenylated benzophenones and a naphthoquinone epoxide (isolated for the first time from a natural source). Three of the major components demonstrated significant antimicrobial activity, and two (obtained as inseparable mixture) possessed radical scavenging activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
143
0
35

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(192 citation statements)
references
References 23 publications
(26 reference statements)
6
143
0
35
Order By: Relevance
“…Group 4A is composed of 3 propolis samples characterized by ion of m/z 601. This ion corresponds to two prenylated benzophenones isolated from red Brazilian propolis and identified by Trusheva et al [37] and which stood out as the major marker ion of red R1 Brazilian propolis in previous ESI-MS studies [19]. The samples in this group were red propolis samples from the states of Alagoas and Amazonas in Brazil, and Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Group 4A is composed of 3 propolis samples characterized by ion of m/z 601. This ion corresponds to two prenylated benzophenones isolated from red Brazilian propolis and identified by Trusheva et al [37] and which stood out as the major marker ion of red R1 Brazilian propolis in previous ESI-MS studies [19]. The samples in this group were red propolis samples from the states of Alagoas and Amazonas in Brazil, and Fig.…”
Section: Resultsmentioning
confidence: 61%
“…A própolis vermelha, cuja origem botânica provém da Dalbergia ecastophyllum, é encontrada na Região Nordeste do Brasil [19][20][21][22] . Suas propriedades biológicas são atribuídas aos flavonoides e aos ácidos fenólicos 19,20,[22][23][24] , destacando-se as ações: anti-inflamatória 25 , citotóxica 23,24,26 , antiaterogênica 27 , cicatrizante 28 , regeneradora de tecido cartilaginoso e pulpar dental 29 , antioxidante 19,22,24,30 e antimicrobiana 19,20,22,30,31 .…”
Section: Um Dos Principais Microrganismos Envolvidos Neste Processo Iunclassified
“…Suas propriedades biológicas são atribuídas aos flavonoides e aos ácidos fenólicos 19,20,[22][23][24] , destacando-se as ações: anti-inflamatória 25 , citotóxica 23,24,26 , antiaterogênica 27 , cicatrizante 28 , regeneradora de tecido cartilaginoso e pulpar dental 29 , antioxidante 19,22,24,30 e antimicrobiana 19,20,22,30,31 . Esta última ação foi observada contra Candida albicans 22 , Staphylococcus aureus 19,22 e Staphylococcus mutans, apresentando resultados positivos, bem como atividade citotóxica.…”
Section: Um Dos Principais Microrganismos Envolvidos Neste Processo Iunclassified
“…In the temperate zone, the seasonal variations in propolis composition are predominantly quantitative, indicating that bees collect propolis from the same group of plants throughout the year (Miguel et al, 2010). However, tropical propolis samples have shown differences in their chemical compositions (Trusheva et al, 2006;Cuesta-Rubio et al, 2007). The present work showed that, despite the local biodiversity, the chemical compositions of the collected propolis did not show much qualitative variation.…”
Section: Discussionmentioning
confidence: 48%
“…Formononetin, is used as a chemical marker (Cuesta-Rubio et al, 2007) for red propolis and has only been identified in red propolis samples from Brazil (Cabral et al, 2009) and Cuba (Cuesta-Rubio et al, 2007). Trusheva et al (2006) also observed the presence of isoflavonoids in Brazilian red propolis. The presence of isoflavonoids in propolis suggests new potential biological applications for this natural product.…”
Section: Discussionmentioning
confidence: 99%